Magnetic Resonance Imaging and Gynecological Devices - Correia, L (2012)
Background: Performing magnetic resonance imaging (MRI) on women with gynecological devices is a completely accepted practice. The goal of our review is to assess how safe it is to perform MRI on women using contraceptive implants or devices. Study Design: Literature review, searching in PubMed-Medline/Ovid for the following keywords: magnetic resonance imaging, intrauterine devices, Implanon® and Essure®. Results: Though plastic devices do not represent a contraindication to the use of the technique, those including metallic components have been submitted to several tests, after which they were classified as MR Conditional (devices presenting no risks in MR-specific environments) by the Food and Drug Administration. Thus, the use of MRI can be safely advised to women with this type of device as long as the magnetic resonance equipment is ≤3.0 T. Conclusions: Presently, there is no scientific evidence that contraindicates performing MRI on women with any kind of gynecological device. Therefore, this procedure is safe as long as it is performed under previously tested conditions.